2004
DOI: 10.1111/j.1365-2141.2004.05200.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential damage and recovery of human mesenchymal stem cells after exposure to chemotherapeutic agents

Abstract: Summary Mesenchymal stem cells (MSCs) are an important cellular component of the bone marrow microenvironment for supporting haemopoiesis. However, their response to high‐dose chemotherapy remains unknown. We assessed the acute direct effects of individual chemotherapeutic agents on human MSCs (hMSCs). Using an in vitro culture system, the chemosensitivity of hMSCs was determined by XTT (2,3‐bis(2‐methoxy‐4‐nitro‐5‐sulphophenyl)‐5‐[(phenylamino) carbonyl]‐2H‐tetrazolium hydroxide) assay in comparison with that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
1
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 41 publications
(52 reference statements)
12
114
1
7
Order By: Relevance
“…Thus, only the higher proliferating, less-affected MSC-derived stromal cultures were used in the comparative analysis between the high-dose and notreatment patient groups in these experiments. Two previous studies have suggested that MSCs are resistant to chemotherapeutic agents at clinically relevant doses [30,42]. In contrast to our study, one focused on the effects of several chemotherapeutic agents used alone in vitro [30]; the other study did however present the effects of chemotherapy on MSCs in vivo but it did not focus on hematopoietic cell support.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, only the higher proliferating, less-affected MSC-derived stromal cultures were used in the comparative analysis between the high-dose and notreatment patient groups in these experiments. Two previous studies have suggested that MSCs are resistant to chemotherapeutic agents at clinically relevant doses [30,42]. In contrast to our study, one focused on the effects of several chemotherapeutic agents used alone in vitro [30]; the other study did however present the effects of chemotherapy on MSCs in vivo but it did not focus on hematopoietic cell support.…”
Section: Discussionmentioning
confidence: 84%
“…Two previous studies have suggested that MSCs are resistant to chemotherapeutic agents at clinically relevant doses [30,42]. In contrast to our study, one focused on the effects of several chemotherapeutic agents used alone in vitro [30]; the other study did however present the effects of chemotherapy on MSCs in vivo but it did not focus on hematopoietic cell support. In addition, while their findings suggest that chemotherapy has no effect on MSC expansion and phenotype, there were several differences between our studies, for example differences in population sizes, experimental methods, times between last chemotherapy administration and bone marrow harvest, and most importantly chemotherapy dose and/or regimens used in the patient cohorts [42].…”
Section: Discussionmentioning
confidence: 84%
“…6 Preliminary data also suggest that fetal MSC can be differentiated along myogenic and neural lineages, and so represent a ready source of human multipotent cells. Although it might be expected that highly proliferative stem cells would be equipped with efficient death machinery, there is little published work on apoptotic signalling pathways in MSC or bone marrow-derived stromal cells, [7][8][9] and even fewer studies of apoptosis in other stem cells. 10 Since apoptosis is a major cause of graft failure, we hypothesised that there would be robust and functional intrinsic and extrinsic apoptotic signalling pathways in naïve human MSC.…”
mentioning
confidence: 99%
“…Apesar da associação com estados patológicos, acredita-se que as funções fisiológicas da P-gp são basicamente o transporte de íons, nutrientes, compostos hidrofóbicos e metabólitos através das membranas celulares, e podem ser encontradas naturalmente em diversos tecidos do organismo adulto, como na barreira hematoencefálica, rins, fígado, intestino, pulmões e células-tronco (Johnstone et al, 2000;Gottesman & Bates, 2002 Koc et al 1999;Tsuruo et al, 2003;Li et al, 2004).…”
Section: 30unclassified
“…A porcentagem de população corada foi estimada, e dentre as linhagens avaliadas, a MES-DX (41,97 ± 5,59 *p=0,0052) mostrou-se superior quando comparadas às células do LA (18,86 ± 3,37) e MO (20,27 ± 3,58), entretanto, não houve diferença estatística entre as CTM. Esta paridade foi ratificada quando relacionada ao IC50, onde a concentração inibitória das células de LA (639,3 ± 84,87) (Li et al, 2004).…”
Section: Exclusão De Rhodamina 123unclassified